Biomonitoring of Malaysian aquatic environments: A review of status and prospects - Prabhakaran, K.; Ramasamy, Nagarajan; Francis, Merlin; Anand Kumar, A. (2017)
Anthropogenic stressors are reported to be the major drivers of aquatic pollution all over the world. Combating aquatic pollution requires adequate monitoring and inventorying mechanisms, and biomonitoring with the help of bioindicator organisms can be regarded as a sensitive tool for the evaluation of the biological and ecological significance of aquatic pollution. Bioaccumulation, biochemical alterations, morphological and behavioural approaches, population and community level approaches, and in vitro toxicity tests of aquatic organisms are all common techniques employed in biomonitoring of aquatic environments. In this review, the body of literature dealing with the pollution via biomonitoring in Malaysian aquatic ecosystems is discussed. It is evident from the study that, in Malaysia, biomonitoring by bioaccumulation received more attention than other biomonitoring techniques. Aquatic ecotoxicological research studies are very limited in east Malaysia (Sabah and Sarawak), when compared to west (Peninsular) Malaysia. The potential applications of biomonitoring and its relevance for the Malaysian aquatic ecosystems are discussed. Recommendations for future improvements in the Malaysian aquatic pollution biomonitoring are also made.